A Musical Offering: Essays in Honor of Martin Bernstein - Bernstein, Martin 1904-1999; Clinkscale, Edward H.; Brook, Claire (New York Pendragon, 1977)
In the great tradition of the German Festschrift, this book brings together articles by Professor Bernstein's colleagues, friends and students to honor him on his 70th birthday. Ranging in subject from the trouvère song through esoteric aspects of Renaissance studies and authenticity in 18th-century musical sources to a lively and irreverent attack on performance practices today, the twenty essays by many of America's most distinguished scholars reflect the breadth and variety of Martin Bernstein's far-reaching interests and demonstrates the vitality and relevance of what is best in musicology today.